qanda-logo
search-icon
root-icon-orangeSímbolos
Problema
solution-image
$f\left(x\right)=\sqrt{5x+2} +e^{3x}+\dfrac {4x} {5}^{+\left(x-2\right)\left(x^{2}+3\right)}$ $g\left(x\right)=-3s$ $sen$ $\left(2x\right)+8x^{4}-\dfrac {cos\left(x\right)} {5}^{+2}$ $-1$ $h\left(x\right)=\dfrac {4x} {3}^{+3tan\left(-2x\right)+cos\left(5x\right)+9}$ $y=\left(7-e^{2x}\right)\left(x^{1/3}+2\right)$ $3-$ $w=\left(x-1\right)^{2}$ $\bar{\left(x-1\right)^{2}} +\dfrac {1} {3x^{4}}^{-2x+2e^{x}+x-4}$
Bachillerato
Cálculo
Búsquedas: 146
Contenido de la pregunta
Me podrían ayudar con derivadas
Solución
answer-user-profile-image
Profesor de Qanda - IvánReyes
answer-reply-image
answer-user-profile-image
Estudiante
Muchas gracias